The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s1516-14392001000200009
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes due to laser surface melting of an AISI 304 stainless steel

Abstract: Several techniques can be used to improve surface properties. These can involve changes on the surface chemical composition (such as alloying and surface welding processes) or on the surface microstructure, such as hardening and melting. In the present work surface melting with a 3kW CO2 cw laser was done to alter surface features of an AISI 304 stainless steel. Microstructure characterisation was done by optical and scanning electron microscopy. Vickers and Knoop microhardness tests evaluated mechanical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…A similar cooling rate is observed in the strip casting process [8]. On the other structures it must be pointed out that the columnar-cellular can be observed in the laser melting, requires a 10 5 K/s cooling rate [9]. The higher estimated cooling rate was 10 6 necessary K/s that explains the presence of ferrite.…”
Section: Results and Commentssupporting
confidence: 72%
“…A similar cooling rate is observed in the strip casting process [8]. On the other structures it must be pointed out that the columnar-cellular can be observed in the laser melting, requires a 10 5 K/s cooling rate [9]. The higher estimated cooling rate was 10 6 necessary K/s that explains the presence of ferrite.…”
Section: Results and Commentssupporting
confidence: 72%
“…These micrographs indicated that laser surface melting resulted in fine solidification structure of the alloys. This could be attributed to the faster cooling rates, developed as a consequence of the temperature gradients generated in the material 31,32 The solidification occurred epitaxially from the boundary between the treated region and the untreated matrix.…”
Section: Resultsmentioning
confidence: 99%
“…According to the optical microscope image obtained at 500× magnification, the microstructure consists of a γ-austenite matrix with δ-ferrite having a dendrite size of about 20 μm. During the solidification of austenitic stainless steel, such as AISI 304 stainless steel, the first phase to solidify as the temperature drops below the point of peritectic transformation is δ-ferrite [46]. Hence, δ-ferrite tends to transform into austenite (γ) during cooling.…”
Section: Finite Element Analysismentioning
confidence: 99%